(untitled) (Revista científica Olimpia, 2019)
In Cuba, since the beginning of 2017 was introduced to the market a new isotonic drink for high performance athletes. In Granma it began to be used in the sports population in June 2017 in a generalized way. Because it is a new product in the market, it is decided to carry out post-marketing pharmacovigilance studiesThe study universe consisted of 253 athletes from sports schools in Granma province who received the Ergoplus, isotonic drink, during the period evaluated. The sample consisted of 120 athletes who met the defined inclusion criteria. The Ergoplus isotonic drink is safe in the studied sample and in a small portion of the sample were reported adverse reactions cataloged as mild manifested primarily as gastrointestinal disorders.